Experience of uncertainty in prostate cancer: A qualitative study - Yingna Li; David Gillanders; Anne Finucane (PLoS ONE, 2025)
Background Prostate cancer is characterised by significant uncertainty, yet men’s lived experience of uncertainty in this context remain underexplored. Existing research has primarily focused on uncertainty related to informational needs, the pre-treatment phase, or men under active observation. Little attention has been paid to uncertainty that extends beyond informational gaps or affects those who have undergone active treatment. Objective This study aimed to address this gap by exploring how men experience uncertainty throughout the prostate cancer journey. Gaining such insight is essential for informing more holistic and responsive care. Methods Individual semi-structured interviews were conducted with 12 men diagnosed with prostate cancer who were either undergoing or had completed active treatment. Data were analysed using reflexive thematic analysis. Results Four overarching themes were developed: (1) Aspects of uncertainty, including ambiguity surrounding the cancer trajectory, interpersonal relationships, and the future; (2) Initial responses to uncertainty, including emotional distress and avoidant behaviours; (3) Managing uncertainty, including strategies used to cope and adapt; and (4) Posttraumatic growth, highlighting positive changes attributed to navigating prostate cancer and its uncertainty. Conclusions Uncertainty is a pervasive and enduring aspect of the prostate cancer experience, extending beyond diagnosis into treatment and survivorship. It complicates psychological adjustment and calls for adaptive management. Support interventions should address not only informational but also emotional and relational dimensions of uncertainty, promoting openness and acceptance, perspective-taking, values-driven living, and dyadic adjustment.